Influenza vaccine effectiveness among primary and secondary school students in Shenzhen during the 2023/24 influenza season - Yawen Jiang; Jiatong Sun; Fang Huang; Xu Xie; Xin Wang; Xiaoliang Wu; Min Jiang; Ying Sun; Hui Liu; Huiqiao Gu; Quan Lu; Xiaozhen Chen; et al. (Emerging Microbes and Infections)
During the winter influenza peaks, a total of 2689 ILI patients were collected from the two hospitals, with 58.61% of the participants vaccinated. Of the ILI patients, 761 (28.3%) were laboratory-confirmed influenza infection, with 76.7% being A(H3N2) and 22.8% B/Victoria. After adjusting for covariates, the adjusted VE (aVE) was 57.06% (95% CI, 48.59–64.13%). In the subtype/lineage and age subgroup analysis, influenza VE against B/Victoria was higher than A(H3N2), and decreased with age. More, influenza VE (aVE = 19.63% [95% CI, −29.13–49.98%]) against all subtypes/lineages were not statistically significant for the spring-summer peak. Overall, influenza vaccines provided significant protection against influenza-associated outpatient visits among students in Shenzhen during 2023/24 winter influenza season. The findings underscore the importance of maintaining high vaccination coverage.